Effect of germanium addition on the properties of reactively sputtered ZrN films - Pilloud, D. (2005)
For the first time, Zr-Ge-N films were deposited on silicon and steel substrates by sputtering a Zr-Ge composite target in reactive Ar-N2 mixture. The films were characterised by electron probe microanalysis, X-ray diffraction, micro-Raman spectroscopy and depth-sensing indentation. The effects of the Ge content and substrate bias voltage on the films' structure, internal stress, hardness and oxidation resistance were investigated. Substrate bias strongly influenced the chemical composition of the films being observed by means of a steep decrease in the Ge content for negative bias voltages higher than -80 V. In these cases, a significant hardness improvement was registered. For -100 V biased films, in the Ge concentrations range tested in this study, only ZrN grains were evidenced by X-ray diffraction. The film compressive stresses increased with the germanium concentration. An unexpected effect of the Ge content on the films' hardness was observed. In spite of the increase in the compressive stresses of the films with increasing Ge content, the hardness monotonously dropped from 38 GPa for pure ZrN down to 21.5 GPa for 4.6 at.% Ge. Addition of Ge into ZrN-based coatings induced an improvement of the oxidation resistance and it favoured the tetragonal form of zirconia in oxidised Zr-Ge-N coatings.